Pengaruh Content Marketing, Electronic Word of Mouth dan Persepsi Harga Terhadap Keputusan Penggunaan Jasa Fotografi di Hagiframe - Muhammad Ihwal Faiq; Wasti Revindani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The service business is currently a growing trend, because many people who are already working but choose to have a side job, namely by offering services according to their skills. Photography is one of the new opportunities in the service and business sector, some people make their hobby in photography into a job that can generate profits. The writing method uses This research was conducted using a qualitative method, providing an overview of the object being studied by using interviews that have been collected as is. The author's goal is to determine whether there is an influence of content marketing, electronic word of mouth (e-WOM) and price perception on buyer decisions. The results obtained from this study are that Hagiframe optimizes through the creation of digital campaigns, Hagiframe provides quality services to leave a positive impression on customers and Hagiframe has a price rate that is relatively cheap and friendly to consumers' pockets. In this case, Hagiframe still has trust in customer decisions to use its services.